Development of Project-Based IPAS Module to Increase Students' Learning Creativity SMKN 1 Gedongtataan - Natalia, Desy; Herpratiwi, Herpratiwi; Widodo, Sugeng; Nurwahidin, Muhammad; Yulianti, Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This research is a development research that aims to analyze; (1) the potential and conditions for developing learning modules, (2) the process of developing project-based IPAS modules (3) module characteristics, (4) module effectiveness, and (5) module attractiveness. This research uses the ADDIE model development design which includes the stages of analysis, design, development, implementation and evaluation. The subjects in this study were 23 students of class X of the Plant Agribusiness Expertise Program of SMK Negeri 1 Gedongtataan. Data collection methods used questionnaires, interviews and tests. The results of this research and development indicate that the potential of students can use modules as learning materials and the condition of infrastructure at SMK Negeri 1 Gedongtataan is very supportive and allows for the development of project-based learning modules, Product criteria after being validated by a team of material experts with a score of 87.67 (very feasible), media experts score 95.29 (very feasible), and design experts score 96.84 (very feasible). The characteristics of the project-based module developed meet the requirements of being self-standing, independent, adaptive and familiar with the user. Based on the results of the t test, the sig result of 0.000 is smaller than the 5% significance level, which means that the use of project-based modules significantly increases students' learning creativity. The developed module is effective for increasing the learning creativity of IPAS students with a normalized gain value of 0.6297 (medium). The attractiveness of the developed module is in the interesting category with a score of 84.5 and the category is easy to use.